Technology adoption, agricultural productivity, and road infrastructure in Bhutan - Minten, Bart; Dukpa, Chencho (International Food Policy Research Institute, 2010)
Agricultural productivity increases are one of the desired outcomes from sensible food security and agricultural policies. Increased productivity might lead to improved welfare of rural populations through several pathways. First, increased productivity ensures higher food availability and higher incomes at the farm household level. Second, increased food availability leads to lower prices of agricultural products and higher real wages, to the benefit of poor net buyers and wage laborers respectively. Third, a well-performing agricultural sector has important economic multiplier effects on the vibrancy of the off-farm rural economy. However, policy makers are often hampered by a lack of information on agricultural productivity, the constraints that farmers face, and the levers that they can use to improve productivity.